Cold storage temperatures and durations affect the concentrations of lupeol, mangiferin, phenolic acids and other health-promoting compounds in the pulp and peel of ripe mango fruit - Vithana, M.; Singh, Zora; Johnson, Stuart (Elsevier, 2018)
© 2018 Elsevier B.V. Mangoes are usually stored above 13 °C to avoid chilling injury. We investigated the effects of cold storage temperatures (5 and 13 °C) and durations (12 and 24 d) on the concentrations of lupeol, mangiferin, phenolic acids (gallic, chlorogenic, vanillic, ferulic and caffeic), ascorbic acid, carotenoids, total phenols and antioxidants in the pulp and peel of ripe ‘Kensington Pride’ mango fruit. Mature green mangoes were stored at 5 °C (chilling) or 13 °C (non-chilling) temperature for 12 and 24 d prior to ripening at ambient temperature (21 ± 1.5 °C). Chilling injury and concentrations of health-promoting compounds were determined at eating soft ripe stage. Chilling injury symptoms were only developed on ripe fruit following storage at 5 °C for 24 d. The concentrations of lupeol in pulp and peel, chlorogenic and caffeic acids in the pulp were significantly higher in fruit stored at 5 °C than 13 °C, whilst mangiferin, gallic, chlorogenic, vanillic, ferulic, and caffeic acids, total phenols, antioxidants and carotenoids in the peel were significantly higher when stored at 13 °C. The concentrations of lupeol and chlorogenic acid in pulp and peel and gallic acid in the pulp were significantly lower when stored for 24 d compared to 12 d, whilst vanillic acid, total phenols, total antioxidants and ascorbic acid in the pulp and caffeic acid in both pulp and peel were significantly higher when stored for 24 d. In conclusion, cold storage temperatures and duration influence the concentration of lupeol, mangiferin, phenolic acids and other health-promoting compounds in the pulp and peel of ripe mango fruit. Storage of mature green mangoes at chilling temperature (5 °C) for 12 d prior to ripening (21 ± 1.5 °C) seems to be a promising tool for maximizing the levels of lupeol in the pulp and peel of the fruit.